2022
DOI: 10.1108/jfbm-06-2022-0086
|View full text |Cite
|
Sign up to set email alerts
|

Family businesses in tourism – the use of digital technologies in times of uncertainty and crisis

Abstract: PurposeThe main purpose of this paper is to explore the impact of digital technologies on the promotion of tourist offer from the perspective of family businesses. The paper tries to provide a better understanding of the factors that determine the use of digital technologies in the family tourism business, both in the modern digital world and in times of uncertainty and crisis caused by the COVID-19 pandemic.Design/methodology/approachThe survey method was used in the realization of the research. Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
0
13
0
2
Order By: Relevance
“…Yström and Agogué (2020) and Melović et al . (2022) investigated the effects of digital technologies on the supply of tourism services from the perspective of family businesses and concluded that the use of digital technologies in tourism is significantly affected by the perceived trends in tourism, the crisis and uncertainty caused by the Covid-19 pandemic and the market actors' perceptions, attitudes and understanding of the specifics and advantages of digital technologies offered to tourists.…”
Section: Theoretical Frameworkmentioning
confidence: 93%
See 1 more Smart Citation
“…Yström and Agogué (2020) and Melović et al . (2022) investigated the effects of digital technologies on the supply of tourism services from the perspective of family businesses and concluded that the use of digital technologies in tourism is significantly affected by the perceived trends in tourism, the crisis and uncertainty caused by the Covid-19 pandemic and the market actors' perceptions, attitudes and understanding of the specifics and advantages of digital technologies offered to tourists.…”
Section: Theoretical Frameworkmentioning
confidence: 93%
“…The tourism industry is one of the largest and fastest growing industries in the global economy, which significantly contributes to employment and gross domestic product (GDP) (Melović et al ., 2022). The tourism industry is also a driver of economic growth (Ye et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Another emerging trend in the tourism industry is identification technologies (Bayram, 2020) that include identification of elements such as fingerprints, facial recognition, retinal scanning and other biometric identification methods, aiming to better ensure security and identify people. Also, such technologies help significantly in collecting data to determine the personality of the tourist, in order to create personalized services or offers to the customer (Melović, Baynazoğlu, & Šerić, 2023). The next digital trend in the tourism industry is the Internet of Things (IoT), a technology that exploits the use of the Internet's capabilities to interface and communicate with the various digital devices with the ultimate goal of more efficient data sending and receiving (Elkhwesky & Elkhwesky, 2023).…”
Section: Current and Future Trendsmentioning
confidence: 99%
“…time, initial and ongoing capital investment, ongoing technical support) required to educate and train staff in continuous level. It should be noted that the tourism industry is mainly based on staff that are temporary and the degree of loyalty to the company is small (Melović, Baynazoğlu, & Šerić, 2023), as a result of which companies and jobs are constantly changing. Another important challenge is linked to the high cost and uncertainty of the investment, as a result of which a large number of tourism businesses, especially family ones, avoid spending to integrate digital innovations into their organization (Cheng et al, 2023).…”
Section: Main Challenges For the Integration Of Digital Innovations I...mentioning
confidence: 99%
See 1 more Smart Citation